Stock Split Saham dan Dampaknya Terhadap Volume Perdagangan dan Abnormal Return Saham - Siti Masyithoh (Owner : Riset dan Jurnal Akuntansi, 2018)
The purpose of this study was to determine significant differences in trading volume and abnormal return before and after event of a stock split. This study was conducted on 19 issuers that do stock split in 2011- 2015 in the Indonesia Stock Exchange withmethod. purposive sampling The analysis technique used is Paired Sample T-Test with the observation period of seven days before and seven days after the stocksplit.From the analysis we found that the volume of stock trading before and after stock split there is no difference significantly, and not finding thedifferences gain abnormal return significant before and after stock split.